Проблема идентичности личности в творчестве Тома Стоппарда - Негляд, Т.А. (Культура народов Причерноморья, 2013)
Проблема идентичности личности занимает первое место в современном мире и является
одной из важнейших проблем на сегодняшний день, что и определяет значимость творчества
английского драматурга Тома Стоппарда.
Ключевые слова: идентичность личности, творчество Тома Стоппарда. Проблема ідентичності особистості займає перше місце в сучасному світі і є однією з
найважливіших проблем на сьогоднішній день, що і визначає значимість творчості англійського
драматурга Тома Стоппарда.
Ключові слова: ідентичність особистості, творчість Тома Стоппарда. Scientific novelty of the work lies in the fact that it was the first in the national literary studies the
problem of personal identity in the works of Tom Stoppard, while the national interest in the literary works of
Tom Stoppard is still local. The problem of personal identity is one of the most important nowadays. It takes
place among the major problems all over the world. It shows the importance of Tom Stoppard creation.
Research methods. The methodological basis of the work is an integrated approach that combines traditional
and new literary methods. Principles of typological approach allow us to formulate the characteristics of
identity in the plays of Tom Stoppard. Creation of the English playwright Tom Stoppard became well known over
the past few decades. Today he became the craftsman of paradoxes, the interpreter of the classics, virtuoso
intelligent, capable and prone to parody reality. Stoppard gained international fame and is recognized as one of
the most significant and most interesting writers of our time. Tom Stoppard is called modern classic, his work
has attracted the attention of many Western scholars of literature and theater critics.
Keywords: personal identity, Tom Stoppard works.